Prognostic impact of peak oxygen uptake and heart rate reserve in patients after off‐pump coronary artery bypass grafting. Issue 4 (25th February 2021) - Abulimiti, Abidan; Nishitani‐Yokoyama, Miho; Shimada, Kazunori; Kunimoto, Mitsuhiro; Matsubara, Tomomi; Fujiwara, Kei; Aikawa, Tatsuro; Ouchi, Shohei; Sugita, Yurina; Fukao, Kosuke; Kadoguchi, Tomoyasu; Miyazaki, Tetsuro; et al.
Abstract: Background: Peak oxygen uptake (peak VO2 ) and heart rate reserve (HRR) are independent prognostic markers of cardiovascular disease. However, the impact of peak VO2 and HRR on long‐term prognosis after off‐pump coronary artery bypass grafting (OP‐CABG) remains unclear. Hypothesis: To determine the prognostic impact of peak VO2 and HRR in patients after OP‐CABG. Results: We enrolled 327 patients (mean age, 65.1 ± 9.3 years; male, 80%) who underwent OP‐CABG and participated in early phase II cardiac rehabilitation. All participants underwent cardiopulmonary exercise testing (CPET) at the beginning of such rehabilitation. Overall, 48 (14.6%) patients died during the median follow‐up period of 103 months. The non‐survivor had significantly lower levels of peak VO2 (10.6 ± 0.5 vs. 13.7 ± 0.2 ml/kg/min, p < .01) and HRR (24.2 ± 1.8 vs. 32.7 ± 0.8 beats/min, p < .01) than the survivor. In both groups, peak VO2 significantly correlated with HRR (p < .01). Moreover, patients were divided into four groups according to the peak VO2 and HRR levels for predicting total mortality. The low‐peak VO2 /low‐HRR group had a significantly higher mortality risk than the other groups (hazards ratio, 5.61; 95% confidence interval, 2.59–12.16; p < .01). After adjusted the confounding factors, peak VO2 and HRR were independently associated with total mortality (both p < .05). Conclusions: HRR is a simple parameter of CPET and an important prognostic marker for the risk stratification of total mortality even in patients with low‐peak VO2 after OP‐CABG.